Abnormal laboratory findings and plasma concentration monitoring of lopinavir and ritonavir in COVID‐19. Issue 3 (3rd August 2020) - Batteux, Benjamin; Bodeau, Sandra; Gras‐Champel, Valérie; Liabeuf, Sophie; Lanoix, Jean‐Philippe; Schmit, Jean‐Luc; Andréjak, Claire; Zerbib, Yoann; Haye, Guillaume; Masmoudi, Kamel; Lemaire‐Hurtel, Anne‐Sophie; Bennis, Youssef
Abstract : It is not known whether the adverse events (AEs) associated with the administration of lopinavir and ritonavir (LPV/r) in the treatment of COVID‐19 are concentration‐dependent. In a retrospective study of 65 patients treated with LPV/r and therapeutic drug monitoring (TDM) for severe forms of COVID‐19 (median age: 67; males: 41 [63.1%]), 33 (50.8%) displayed a grade ≥2 increase in plasma levels of hepatobiliary markers, lipase and/or triglycerides. A causal relationship between LPV/r and the AE was suspected in 9 of the 65 patients (13.8%). At 400 mg b.i.d., the plasma trough concentrations of LPV/r were high and showed marked interindividual variability (median [interquartile range]: 16, 600 [11, 430–20, 842] ng/ml for lopinavir and 501 [247–891] ng/ml for ritonavir). The trough lopinavir concentration was negatively correlated with body mass index, while the trough ritonavir concentration was positively correlated with age and negatively correlated with prothrombin activity. However, the occurrence of abnormal laboratory values was not associated with higher trough plasma concentrations of LPV/r. Further studies will be needed to determine the value of TDM in LPV/r‐treated patients with COVID‐19.